EFL STUDENTS’ ATTITUDES TOWARDS ACADEMIC READING IN WRITING FOR INTERNATIONAL PUBLICATION - Mudra, Heri (ELTR Journal, 2024)
Although academic reading has gained positive attention in EFL classrooms, very little research has been undertaken regarding the descriptive relationship between such types of reading attitudes and article writing. This study focused on determining the academic reading attitudes of EFL students who were writing an article for an international journal. A total of 173 undergraduate and magister students enrolled in an EFL major voluntarily participated in the survey study. By using the AR attitude scale, the survey was undertaken via an online app (e.g., Google Form). The results reveal that there are three dimensions of students’ AR. Behavior factor seems to be negative for the students who read academic texts. They encountered difficulties in comprehending the texts during the article writing process. They believed in AR benefits for article writing, but most students were not confident in their reading competence. In short, AR has important values in developing article writing quality, but strategies are needed to fulfill the expectation.